Effects of feeder design (conventional dry vs. wet-dry) on growth performance of 45- to 246-lb pigs - Nitikanchana, S.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 1,253 pigs (PIC 1050 × 337; initially 45 lb) were used in a 104-d study to evaluate the effects of using a wet-dry (WD) or conventional dry (CD) feeder on growth performance of growing-finishing pigs. At the start of the trial, pens of pigs were weighed and randomly allotted to 1 of the 2 feeder types. The CD feeder was a single-sided, 56-in.-wide, stainless steel feeder (Thorp Equipment, Inc., Thorp, WI) with 4 14-in. feeding spaces and a 4.25-in.-deep trough. A cup waterer in pens using CD feeders ensured ad libitum access to water as well as feed. The WD feeder was double-sided (15-in.-wide feeder opening on each side) with a single nipple waterer (Crystal Springs, GroMaster, Inc., Omaha, NE), and the feeder was the only source of water. All pigs were fed the same corn-soybean meal diets containing 30% bakery by-product and 10 to 45% dried distillers grains with solubles (DDGS) during 5 dietary phases. For the overall period, pigs fed with the WD feeder had greater ADG (P < 0.01) and ADFI (P = 0.01) with no differences in F/G (P = 0.50) compared with pigs fed using the CD feeder. This study confirms previous results where pigs fed using a WD feeder have greater ADG and ADFI than those fed with a CD feeder.
Keywords: Swine; Conventional dry feeder; Wet-dry feeder; Finishing pig